2009
DOI: 10.1111/j.1574-6976.2008.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic approaches to biodegradation

Abstract: Biodegradation, the ability of microorganisms to remove complex chemicals from the environment, is a multifaceted process in which many biotic and abiotic factors are implicated. The recent accumulation of knowledge about the biochemistry and genetics of the biodegradation process, and its categorization and formalization in structured databases, has recently opened the door to systems biology approaches, where the interactions of the involved parts are the main subject of study, and the system is analysed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 74 publications
0
19
0
1
Order By: Relevance
“…In order to fully elucidate microbial ecosystems, however, mathematical approaches will be further combined with other analyses, e.g. , artificial neural networks (40), network theory (61), and systems analysis (63, 64). Systems analysis has been applied to several fields, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In order to fully elucidate microbial ecosystems, however, mathematical approaches will be further combined with other analyses, e.g. , artificial neural networks (40), network theory (61), and systems analysis (63, 64). Systems analysis has been applied to several fields, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics is being successfully used for identification of novel metabolites that bacteria produce when undergoing a stress response. Systems biology approach is now giving new insights into the biodegradation process [86]. The biodegradation process can be considered as a multidirectional network, with the diverse microbial communities interacting with each other and with the environmental factors.…”
Section: Desired Community and Its Performancementioning
confidence: 99%
“…These studies revealed that the catabolism of anaerobic aromatic compounds is more diverse and widespread than previously thought and involves complex metabolic and stress processes (Carmona et al 2009 ) . Systems biology approaches to biodegradation, where the system is analysed as a whole and the interactions amongst the involved parts are the main subject of study, have provided the global analysis of the biodegradation metabolic network in the form of structure, behaviour and evolution (Trigo et al 2009 ) . Advances have been made for enhanced inorganic chemical bioremediation and organic chemical biodegradation using various pathway-engineering approaches that harness molecular, genetic, microbiology, and protein engineering tools.…”
Section: Introductionmentioning
confidence: 99%